Evidence for Better Lives Study: a comparative birth-cohort study on child exposure to violence and other adversities in eight low- and middle-income countries - foundational research (study protocol). Issue 10 (10th October 2020) - Valdebenito, Sara; Murray, Aja; Hughes, Claire; Băban, Adriana; Fernando, Asvini D; Madrid, Bernadette J.; Ward, Catherine; Osafo, Joseph; Dunne, Michael; Sikander, Siham; Walker, Susan P; Thang, Vo Van; et al.
Abstract : Introduction: Violence against children is a health, human rights and social problem affecting approximately half of the world's children. Its effects begin at prenatal stages with long-lasting impacts on later health and well-being. The Evidence for Better Lives Study (EBLS) aims to produce high-quality longitudinal data from cities in eight low- and middle-income countries—Ghana, Jamaica, Pakistan, the Philippines, Romania, South Africa, Sri Lanka and Vietnam—to support effective intervention to reduce violence against children. EBLS-Foundational Research (EBLS-FR) tests critical aspects of the planned EBLS, including participant recruitment and retention, data collection and analysis. Alongside epidemiological estimates of levels and predictors of exposure to violence and adversity during pregnancy, we plan to explore mechanisms that may link exposure to violence to mothers' biological stress markers and subjective well-being. Methods and analyses: EBLS-FR is a short longitudinal study with a sample of 1200 pregnant women. Data are collected during the last trimester of pregnancy and 2 to 6 months after birth. The questionnaire for participating women has been translated into nine languages. Measures obtained from mothers will include, among others, mental and physical health, attitudes to corporal punishment, adverse childhood experiences, prenatal intimate partner violence, substance use and social/community support. Hair and dry blood spot samples are collected from the pregnant women to measure stress markers. To explore research participation among fathers, EBLS-FR is recruiting 300 fathers in the Philippines and Sri Lanka. Ethics and dissemination: The study received ethical approvals at all recruiting sites and universities in the project. Results will be disseminated through journal publications, conferences and seminar presentations involving local communities, health services and other stakeholders. Findings from this work will help to adjust the subsequent stages of the EBLS project.